Pencegahan balita stunting melalui edukasi makanan pendamping air susu ibu (MPASI) yang inovatif - Hermilasari, Rista Dwi; Viranda, Rizkyana Surya; Astarina, Nesya; Mustika, Auraning; Aulia, Amanda Kharismatul; Swardiyanti, Gusfiana Dwi; Ibrahim, Zadam Maulana (INDRA: Jurnal Pengabdian kepada Masyarakat, 2025)
Complementary feeding (MPASI) is additional food used to meet the growth and development needs of babies under 5 years old after 6 months. Complementary feeding given early to babies before the age of 6 months has the risk of causing stunting. Early provision of complementary feeding to babies under 6 months of age in Tangsil Wetan Village, Bondowoso Regency is 16.5%. Bondowoso Regency is one of the areas in East Java with a high prevalence of stunting in 2024 of around 32%. This community service activity aims to provide education on providing innovative complementary feeding to mothers of toddlers in Tangsil Wetan Village to prevent stunting. This community service activity uses lecture, question and answer, and demonstration methods. Participants who participated in the counseling activities were given a pretest and a posttest to measure their level of knowledge. The pretest and posttest results showed that mothers' knowledge after being given counseling increased significantly (p<0.05). In addition, demonstrating the right MPASI menu texture according to the toddler's age in this community service activity can be a preventive effort against stunting incidents in Tangsil Wetan Village.